2011
DOI: 10.1007/s11120-010-9617-x
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines stimulate non-photochemical quenching of chlorophyll a fluorescence in Scenedesmus obliquus

Abstract: Polyamines (PAs) are small metabolites that are produced and oxidized in chloroplasts with an obscure mode of action. Recently, we showed that qE is stimulated by PAs in higher plants (Nicotiana tabacum) and in genetically modified plants with elevated thylakoid-associated PAs (Ioannidis and Kotzabasis Biochim Biophys Acta 1767:1371-1382, 2007; Ioannidis et al. Biochim Biophys Acta 1787:1215-1222, 2009). Here, we investigated further their quenching properties both in vivo in green algae and in vitro is isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 50 publications
3
18
0
2
Order By: Relevance
“…1B, trace d). This confirms earlier works of our group showing quenching of antenna isolated from algae and plants by Spm (Ioannidis et al, 2011;Tsiavos et al, 2012). The emerging pieces of the NPQ puzzle include LHCII , Lut [present work and (Ruban et al, 2007)], polyamines [present work and Ioannidis and Kotzabasis (2007) Kotakis et al (2014)], pH (Müller et al, 2001) and C4-C5-C6 conformational changes (Pandit et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…1B, trace d). This confirms earlier works of our group showing quenching of antenna isolated from algae and plants by Spm (Ioannidis et al, 2011;Tsiavos et al, 2012). The emerging pieces of the NPQ puzzle include LHCII , Lut [present work and (Ruban et al, 2007)], polyamines [present work and Ioannidis and Kotzabasis (2007) Kotakis et al (2014)], pH (Müller et al, 2001) and C4-C5-C6 conformational changes (Pandit et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Recently, it was shown that tobacco plants over-expressing a maize chloroplast transglutaminase have about double the thylakoid-associated polyamines and increased qE in comparison to the wild type (Ioannidis et al, 2009). Moreover, in isolated LHCII from green algae and plants, spermidine and Spm increase fluorescence quenching at 680 nm (Ioannidis et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Similar aggregation induced quenching can be also caused by chemicals having strong effects of membrane impermeable cations such as the polyamines (e.g., petruscine, spermidine, and spermine) on Chl a fluorescence quenching (Ioannidis and Kotzabasis, 2007). These organic compounds are synthesized by living cells, and they can quench the maximal fluorescence in the dark and stimulate NPQ in light in vivo in higher plants (Ioannidis and Kotzabasis, 2007; Ioannidis et al, 2012) and in algae (Ioannidis et al, 2011). This simulation of NPQ seems to be due to antenna aggregation (Tsiavos et al, 2012).…”
Section: Regulatory Role Of Protons and Ions In Triggering Non-photocmentioning
confidence: 99%
“…The three major polyamines, putrescine (PUT), spermine (SPM) and spermidine (SPD) have been reported to have roles in many biological processes such as cell division, growth and senescence (Igarashi & Kashiwagi, 2000). Their involvement in acclimation processes of PSII such as the down regulation of antenna size, increases in nonphotochemical quenching and ROS scavenging during light stress suggest important photoprotective roles (Groppa & Benavides, 2008;Ioannidis et al, 2011). For macroalgae, the involvement of polyamines in UV stress responses has been examined in very few studies indicating that UV-B exposure can increase the amounts of polyamines (mainly PUT) up to 200% as reported for the red alga Porphyra cinnamomea (Schweikert et al, 2011).…”
Section: Polyaminesmentioning
confidence: 99%